Virtual game Changers: how avatars and virtual coaches influence exergame outcomes through enactive and vicarious learning. Issue 7 (19th May 2022) - Li, Benjamin J.; Ratan, Rabindra; Lwin, May O.
ABSTRACT: Exergames offer both enactive and vicarious learning through the graphical representations of the self and virtual coach. This study established and tested a model of exergame motivation with Social Cognitive Theory as the foundation. A 2 (User Avatar: Absent versus Present) × 2 (Virtual Coach: Absent versus Present) between-subjects experiment was conducted with 137 high school students. Results supported a model in which the user avatar led to identification, with the relationship mediated by self-presence. Playing with a virtual coach increased social presence. Both identification and social presence were significantly related to future exercise intention, with the relationships mediated by in-game competence. These findings suggest notable theoretical and practical implications of using self-presence with avatars and social presence with virtual agents to enhance exergame outcomes through enactive and vicarious learning.